2017
DOI: 10.1007/s11042-017-4522-3
|View full text |Cite
|
Sign up to set email alerts
|

Tree-based modelling for the classification of mammographic benign and malignant micro-calcification clusters

Abstract: Computer Aided Detection (CAD) systems are being developed to assist radiologists in diagnosis. For breast cancer the emphasis is shifting from detection to classification of abnormalities. The presented work concentrates on the benign versus malignant classification of micro-calcification clusters, which are a specific type of mammographic abnormality associated with the early development of breast cancer. After segmentation (automatic or manual), tree-based representations were used to distinguish between be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Yang et al 14 employed the Simplified Pulse Coupled Neural Network (SPCNN) to classify each case based on wavelet high-frequency coefficients and reported an AU C = 0.97 with an accuracy of over 93% tested on both the MIAS and Japanese Society of Medical Imaging Technology datasets. Suhail et al 15 used a binary tree-based approach to model the clinical perception features such as the number of microcalcifications and the distribution pattern; which can be mathematically computed based on the topology of the trees and the connectivity of the microcalcifications. The authors reported 91% accuracy based on 288 patches extracted from the DDSM dataset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yang et al 14 employed the Simplified Pulse Coupled Neural Network (SPCNN) to classify each case based on wavelet high-frequency coefficients and reported an AU C = 0.97 with an accuracy of over 93% tested on both the MIAS and Japanese Society of Medical Imaging Technology datasets. Suhail et al 15 used a binary tree-based approach to model the clinical perception features such as the number of microcalcifications and the distribution pattern; which can be mathematically computed based on the topology of the trees and the connectivity of the microcalcifications. The authors reported 91% accuracy based on 288 patches extracted from the DDSM dataset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proposed method for MC cluster classification was compared with other relevant publications (see Table 7 ). Akram et al [ 12 ] proposed a tree-based representations for MC clusters, where scale-invariant topological features of MC were extracted showing 91% accuracy for cluster classification. Although high accuracy was achieved, the performance for MC cluster classification on digital mammogram was not reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Double reading can improve sensitivity, but a lack of experienced radiologists can be a challenge [ 9 ]. CADx can assist radiologists in detecting abnormalities in an efficient way [ 10 , 11 ] and systems have been developed to provide a second opinion for diagnosis [ 12 ]. Previous studies have developed computerized methods to aid the diagnosis of MC clusters.…”
Section: Introductionmentioning
confidence: 99%